Implementasi Sosial Media Marketing Cv.Padang Gadget Indonesia Cabang Solok Melalui Sosial Media Instagram Pada Program Akhir Tahun 2023 - Akbar, Taufiq Muhammad; Flowerina, Indria (CV. ITTC INDONESIA, 2024)
This research aims to identify the implementation of social media marketing on the Solok branch of CV. Padang Gadget Indonesia via social media Instagram at the end of 2023 program, both in terms of strategy, implementation, and challenges. The social media marketing strategy implemented by CV. Padang Gadget Indonesia Solok branch is to improve brand awareness, increase sales, and expand market reach. As one of the most massive sources of information, social media is a very effective and efficient marketing channel. To describe this research, researchers used the AIDDA theory. In this theory there are 5 (five) stages / social media marketing strategies, namely Attention, Interest, Desire, Decision, and Action. This research uses descriptive qualitative methods, research that produces descriptive data in the form of writing or speech, as well as the behavior of people being observed. This method is applied to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. CV. Padang Gadget Indonesia Solok branch has implemented the AIDDA theory in the social media marketing strategy they implement. For each content produced for each AIDDA theory, CV. Padang Gadget Indonesia Solok branch focuses on 3 (three) important points, which are the choice of appearance/design and content that suits the target market and a consistent narrative. In the end of 2023 program, social media marketing implementation strategy of CV. Padang Gadget Indonesia Solok branch succeeded in showing positive results. This can be seen from the increase in sales and improvements in insight on social media Instagram @padanggadget_solok. Meanwhile, the obstacle faced is managing the content creation schedule. The strategies implemented are also always evaluated at the end of each month or each program. Through this strategy, CV. Padang Gadget Indonesia Solok branch is able to become the top-of-mind and remains the main choice for their target.